Analysis of Figurative Language in the Lyrics of the Song Anaheim by Niki Zefanya - Wiwin Handayani; Otong Setiawan Djuharie; Deni Suswanto (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to analyze and determine the types of figurative language in the lyrics of Anaheim by Niki Zefanya using a descriptive qualitative approach by presenting the object of analysis and explaining it. In this study, the author will analyze the types of figurative language used in the lyrics of Anaheim by Niki Zefanya and explain the meaning conveyed by the lyrics. The analysis results show that the use of figurative language in the song Anaheim is dominated by metaphors and hyperbole. The use of metaphors and hyperbole in this song conveys emotions, sadness, and feelings of guilt, which are successfully conveyed through the use of figurative language. Thus, figurative language enriches and beautifies language and provides creative expression for songwriters or other creators.